Odpowiedzi

2009-10-08T17:42:42+02:00
A) 5y - 3t + 1 dla y = -4, t = -1
5(-4) - 3(-1) + 1 = -20 +3 + 1 = -16
b) 4a - 3b + 2c -3 dla a = -3, b = 1
4(-3) - 3(1) + 2c - 3 = -12 - 3 + 2c - 3 = - 18 + 2c
c) x² - y² dla x = 1, y = -1
1² - (-1)² = 1 - 1 = 0
d) √x² - 2y² + 3z⁴ dla x = -7, y = 2
√(-7)² - 2(2)² + 3z⁴ = √49 - 8 + 3z⁴ = 7 - 8 + 3z⁴ = -1 + 3z⁴
e) 2x - y + xy dla x = 3, y = 2
2(3) - 2 + ( 3 * 2 ) = 6 - 2 + 6 = 10
f) x² - y² dla x = 1, y = -1
1² - (-1)² = 1 - 1 = 0
  • Użytkownik Zadane
2009-10-08T17:56:25+02:00
A)5*(-4)-3*-1 +1=-20+5= -15
b)4*(-3)-3*1+2c-3=-12-3+2c-3=
2c=-18/:2
C=(-9)
c)1²-(-1)²=1

d) √-7²-2*2²+3z=√49-2*4+3z=7-8+3z=7-8+3z=-1+3z
3z=-1
Z=(-0,33)

e)2*3-2+3*2=6-2+6=10

f) 1²-(-1)²=1
Najlepsza Odpowiedź!
2009-10-08T18:03:18+02:00
A) 5y - 3t + 1 dla y = -4, t = -1
5(-4) - 3(-1) + 1 = -20 +3 + 1 = -16

b) 4a - 3b + 2c -3 dla a = -3, b = 1
4(-3) - 3(1) + 2c - 3 = -12 - 3 + 2c - 3 = - 18 + 2c

c) x² - y² dla x = 1, y = -1
1² - (-1)² = 1 - 1 = 0

d) √x² - 2y² + 3z⁴ dla x = -7, y = 2
√(-7)² - 2(2)² + 3z⁴ = √49 - 8 + 3z⁴ = 7 - 8 + 3z⁴ = -1 + 3z⁴

e) 2x - y + xy dla x = 3, y = 2
2(3) - 2 + ( 3 * 2 ) = 6 - 2 + 6 = 10

f) x² - y² dla x = 1, y = -1
1² - (-1)² = 1 - 1 = 0